Democratization and civilian control in Asia - Croissant, Aurel 1969-; Kuehn, David; Lorenz, Philip; Chambers, Paul W. (Critical studies of the Asia Pacific series, 2013)
How can civilians in newly democratised countries ensure their control over the military? While establishing civilian control of the military is a necessary condition for a functioning democracy, it requires prudent strategic action on the part of the decision-makers to remove the military from positions of power and make it follow their orders